Skepticism as a Mediating Mechanism in the Relationship between Sustainability Literacy and Students' Green Consumption Behavior - Muhammad Shidiq Al Mutawakkil; Muhammad Taufik; Nurbiah; Linda Arisanty Razak; Ismail Badollahi (Universitas Dehasen Bengkulu, 2026)
This study examines the influence of sustainability literacy on green consumption behavior among university students and tests the mediating role of green skepticism. Using a quantitative explanatory approach with a cross-sectional survey of 100 active students at Indonesian universities, data were analyzed via PLS-SEM (SmartPLS). Outer model evaluation confirmed convergent validity (factor loading ≥ 0.651; AVE > 0.59) and construct reliability (CR > 0.94; CA > 0.93). Inner model results demonstrate: sustainability literacy positively and significantly affects green consumption behavior (β = 0.484; t = 5.480; p < 0.001) and green skepticism (β = 0.648; t = 8.150; p < 0.001); green skepticism positively and significantly affects green consumption behavior (β = 0.386; t = 4.120; p < 0.001); and green skepticism partially mediates the relationship (β indirect = 0.250; 95% CI = [0.146; 0.352]). R² = 0.625 indicates substantial predictive power. Findings confirm that knowledge-based green skepticism functions as a catalyst for selective green consumption, not a barrier.